Scientific diasporas and the advancement of science diplomacy: The InFEWS US-China program in the face of confrontational “America First” diplomacy - Prieto, Julian; Scott, Christopher A. (Frontiers in Research Metrics and Analytics, 2022)
The challenges and consequences of climate change have brought together governments around the world to advance scientific knowledge and programmatic actions to develop mitigation strategies while promoting sustainable development. The United States and China – the countries with the highest science expenditures globally – have historically developed a range of joint international research collaborations. However, under the ‘America First’ agenda put forth by the Trump Administration, bilateral diplomatic relations with China reached their highest confrontational peak. Under this scenario science diplomacy served as a catalyst to maintain scientific collaborations between both countries. In 2018, the US National Science Foundation and the China National Natural Science Foundation launched the InFEWS US-China program to promote collaborations to expand food, energy, and water nexus (FEW Nexus) research and applications. Over the past four years, 20 research projects have been awarded from the US side and 47 publications have been reported as research output. By carrying out a descriptive analysis of the InFEWS US-China research and scholarly outputs, we find evidence of the crucial role played by the Chinese scientific diaspora who led 65% of the projects awarded. We find that there is a generally good understanding of the interdependencies between FEW systems included in the project abstracts. However, in the InFEWS US-China scholarly outputs generated to date, there is a lack of usage of a clear FEW Nexus theoretical framework. Further research should address intentional policies that enhance the involvement of scientific diasporas in their home countries to better address climate, sustainability, and development challenges.